Lily the lost puppy - Dale, Jenny; Rodgers, Frank (New York : Aladdin Paperbacks, 2000)
When Lily's family moves, they leave her behind by mistake. Will Lily ever see her family again?
First published in 1999 by Macmillan Children's Books U.K.
"Activity fun pages inside!"
Ages 6-8.
Keywords: Puppies -- Juvenile fiction